INTRODUCTION OF ARTIFICIAL INTELLIGENCE ACHIEVEMENTS – A PREREQUISITE FOR LABOR MARKET TRANSFORMATION - Chudayeva, Iia; Dmitruk, Boris (Social Economics, 2022)
The article presents the theoretical and methodological foundations of artificial intelligence. It is noted that artificial intelligence solves the main problem of health care successfully - overload and shortage of personnel. The reasons for the rapid development of robotization processes in industrialized countries in many branches and spheres of production and the ability of robots to replace workers and office workers and threaten people with job loss are investigated. Attention is focused on need for self-education and retraining of workers, and their ability to work in the conditions of the fourth industrial revolution, and of course, obstacles that stand in the way of the implementation of artificial intelligence achievements. Catastrophic lagging of Ukraine in the field of robotics from the industrialized countries of the world, and the need for a significant acceleration of robotics processes in the main branches of production and in the service sector are emphasized. The transformation of artificial intelligence into a universal resource is accelerated due to the emergence of new tools that make this technology accessible to a wide range of people, and to those who do not have a special education. It is evident that robots will not be able to apply for professions that require creativity, empathy, and communication skills. However, artificial intelligence threatens the middle class, specialists, employees, and office workers. In order not to lose their jobs, many people will need to retrain on online educational platforms, where any person who is sufficiently proactive and capable of mathematics can acquire basic knowledge through educational portals and software tools, which will make deep learning more accessible.  Therefore, there is a chance to have a well-paid job and start a fruitful career, taking into account the requirements of the market. The implementation of artificial intelligence achievements opens up great opportunities for the introduction a whole series of tasks facing society in many spheres of people’s lives.